(untitled) (PANGEEA, 2025)
Record optimization of transactions of Cadastre and Land Book. Since ancient times people have needed records carrying information on the various activities considered critical. At first these records are kept private for each family following that with the development company to take them centrally. The man was shown good ground, it is not of particular interest to the owners but the form of state organization to obtain tax, which is why in this paper the author intends to present both evolution and current level of computerization of operations and Land Book